Cyclodextrin Cavity‐Induced Mechanistic Switch in Copper‐Catalyzed Hydroboration. (2nd August 2017) - Zhang, Pinglu; Meijide Suárez, Jorge; Driant, Thomas; Derat, Etienne; Zhang, Yongmin; Ménand, Mickaël; Roland, Sylvain; Sollogoub, Matthieu
Abstract: N ‐heterocyclic carbene‐capped cyclodextrin (ICyD) ligands, α‐ICyD and β‐ICyD derived from α‐ and β‐cyclodextrin, respectively give opposite regioselectivities in a copper‐catalyzed hydroboration. The site‐selectivity results from two different mechanisms: the conventional parallel one and a new orthogonal mechanism. The shape of the cavity was shown not only to induce a regioselectivity switch but also a mechanistic switch. The scope of interest of the encapsulation of a reactive center is therefore broadened by this study.